The influence of social media towards undergraduate students in Malaysia to travel: web 2.0 - Arif, Muhammad Nabel Asyhar; Saad, Mazni (2019)
In this modern era, the existence of technologies has led to an increase in the usage by internet users on social media and the general advance of new technology internationally. Social media can be described as an electronic communication tool where the users share their information, ideas, personal messages and videos around the world. This study examines factors that the influence of social media towards undergraduates’ students in Malaysia to travel. Using the conceptual framework, the study aims at investigating the possible reasons why undergraduates’ students are influenced by the social media platform to travel. There is issue arise towards the information on social media where the trustworthiness of the sources of information that can be gain by the users, throughout the consumer’s opinion, where thoughts and expressions are not well presented that leads to bad impressions and unfair criticism which arising from ethical issues from using social media. The study uses online questionnaire and quantitative data to collect data. The responses gathered for this study were a total of 54 respondents. The result of the data was analyzed and discussed using IBM-SPSS statistical analysis for this research paper which shows that there is a positive relationship between variables of this study